Improvement of the efficiency of solar thermal energy storage systems by cascading a PCM unit with a water tank. (1st February 2020) - Huang, Haotian; Xiao, Yimin; Lin, Jianquan; Zhou, Tiecheng; Liu, Yanan; Zhao, Qian
Abstract: For solar heating systems, adding phase change material (PCM) can significantly increase the thermal storage capacity. This paper proposes a system using a PCM thermal storage unit cascadely combined with a water tank and configures a composite PCM suitable for the system. This study investigates the impact of this system configuration on the system efficiency while developing a matching principle between components. The system model is built using TRNSYS software; considering the supercooling property, a numerical calculation program of the PCM unit is compiled and verified. The optimal parameters of the PCM are studied by simulations. Finally, sodium acetate trihydrate mixtures are configured and selected as the PCM. The results show that the phase change temperature range suitable for conventional heating systems is 47.5–57.5 °C. The combined use of the PCM unit and water tank can increase the efficiency of the heat storage system. The optimal volume ratio of the PCM unit is 0.67–0.78. Compared with a single water tank system, the solar fraction of the series system can be increased by approximately 30%. Compared with a water tank-PCM unit parallel system, the PCM in the series system effectively increases the system heat collection and enhances the solar fraction by 5%–12%. Highlights: Numerical model of a shell-and-tube PCM storage unit considering the supercooling. A cascaded PCM storage unit with a water tank can improve the system efficiency. The optimum parameters of the PCM in solar heating systems were determined. Compare the efficiency of series system, parallel system and single tank system.